Chronic Anxiety- and Depression-Like Behaviors Are Associated With Glial-Driven Pathology Following Repeated Blast Induced Neurotrauma - Dickerson, Michelle R.; Murphy, Susan F.; Urban, Michael J.; White, Zakar; VandeVord, Pamela J. (Frontiers in Behavioral Neuroscience, 2021)
Long-term neuropsychiatric impairments have become a growing concern following blast-related traumatic brain injury (bTBI) in active military personnel and Veterans. Neuropsychiatric impairments such as anxiety and depression are common comorbidities that Veterans report months, even years following injury. To understand these chronic behavioral outcomes following blast injury, there is a need to study the link between anxiety, depression, and neuropathology. The hippocampus and motor cortex (MC) have been regions of interest when studying cognitive deficits following blast exposure, but clinical studies of mood disorders such as major depressive disorder (MDD) report that these two regions also play a role in the manifestation of anxiety and depression. With anxiety and depression being common long-term outcomes following bTBI, it is imperative to study how chronic pathological changes within the hippocampus and/or MC due to blast contribute to the development of these psychiatric impairments. In this study, we exposed male rats to a repeated blast overpressure (~17 psi) and evaluated the chronic behavioral and pathological effects on the hippocampus and MC. Results demonstrated that the repeated blast exposure led to depression-like behaviors 36 weeks following injury, and anxiety-like behaviors 2-, and 52-weeks following injury. These behaviors were also correlated with astrocyte pathology (glial-fibrillary acid protein, GFAP) and dendritic alterations (Microtubule-Associated Proteins, MAP2) within the hippocampus and MC regions at 52 weeks. Overall, these findings support the premise that chronic glial pathological changes within the brain contribute to neuropsychiatric impairments following blast exposure.